Influence of teratogenic factors on embryonic heart development - Marchenko, D.G.; Morozova , S.B.; Paltov , Ye.V.; Pokhyl , A.V.; Smolkova , O.V. (Морфологія / Morphologia / Morfologìâ, 2025)
One of the key requirements of everyday perinatal medicine is to minimize the teratogenic effect on fetal organogenesis, especially in the cardiovascular system. The heart, the primary functionally active organ of the embryo, begins to form and quickly become noticeable already in the third term of pregnancy, passing through strictly regulated morphogenetic stages. Some exogenous teratogenic mixtures containing ethanol have high penetrability through the placental barrier and polysystemic cytotoxicity. Despite large-scale preventive measures, alcohol consumption during the period of vagitality affects the current problem, since the cause of congenital diseases (CVD) is the cause of neonatal mortality and infection. This article is aimed at analyzing the pathogenetic mechanisms of cardiogenesis disorders under the influence of ethanol, including disorders of clinical proliferation, apoptosis, myofibrilogenesis and epigenetic regulation. The data we selected for the literature review suggest the need for a multidisciplinary approach to early diagnosis, prenatal prevention, and interventions to reduce the risk of cardiovascular injury within the spectrum of fetal alcohol consumption.